Dismissals under industrial law in the private sector in peninsular Malaysia / Manjeet Kaur. - Manjeet , Kaur (1978)
the purpose of this dissertatim is to study and review the law xelating to the dismissals of the employees in the private sector in Peninsular Malaysia. Through the law of the subject it not of recent vintage, its importance has grown repidly in recent years.